Shrub encroachment in Mediterranean silvopastoral systems: Retama sphaerocarpa and Cistus ladanifer induce contrasting effects on pasture and Quercus ilex production - Rivest, David; Rolo, Víctor; López-Díaz, Lurdes; Moreno, Gerardo (Agriculture, Ecosystems & Environment, 2011)
Silvopastoral systems are threatened worldwide by progressive loss of either tree cover or herbaceous cover due to lack of tree regeneration and shrub encroachment, respectively. Grazed Mediterranean open woodlands, as Iberian dehesa, are an outstanding example of silvopastoral system where shrub encroachment has been proposed as an effective means to facilitate tree seedling recruitment and ensure the system persistence. Shrubs also may interact with pasture understorey and tree overstorey, thereby affecting the overall system productivity. We tested the effects of shrub encroachment on pasture yield, tree growth and acorn production in years of contrasting rainfall in Quercus ilex L. dehesas of centralwestern Spain.We compared the effects oftwo prominentMediterranean shrub species that differ in their ecological strategies: a N2-ﬁxing and sparse deep-rooting shrub (Retama sphaerocarpa (L.) Boiss), and a dense shallow-rooting shrub (Cistus ladanifer L). In intermediate and dry years, pasture yield beneath tree canopy was lower by 21–35% than in open grassland. Pasture yield beneath tree canopy was not signiﬁcantly affected during the wet year. C. ladanifer encroachment signiﬁcantly reduced pasture yield by 68–98%, tree growth by 17–29%, and acorn yield by 6–44%. In contrast, R. sphaerocarpa signiﬁcantly increased pasture yield by 11–157% and tree growth by 6–13%, but had a neutral effect on acorn yield. Our results suggest that pasture is more sensitive to shrub encroachment and annual rainfall variation than is Q. ilex. The importance of C. ladanifer competition and R. sphaerocarpa facilitation on pasture yield increased in the driest year. We conclude that the sign and intensity of shrub encroachment effects on pasture and tree production in Mediterranean dehesas are species-speciﬁc and depend on temporal variation as a function of climate.
Keywords: acorn; Agroforestry; competition; Dehesa; Facilitation; Overstorey–understorey interactions